Suplementos nutricionais no Transtorno do Espectro Autista: um relato de caso (Revista Brasileira Multidisciplinar, 2024)
Introduction: Studies have shown that the use of nutritional supplements can bring great benefits in reducing the symptoms of Autism Spectrum Disorder (ASD). In addition, it is known that the drugs approved for use in the treatment of ASD provide partial relief of symptoms and can cause physical and/or psychological dependence, in addition to important adverse reactions. Objectives: To report the benefits of prescribing supplements for a pediatric patient with ASD, during an intervention performed by a pharmacist. Methods: After parental consent, the data recorded in the health facility's system were analyzed. The data presented refer to the period from October 2021 to March 2022. The main data analyzed were: diagnosis, symptoms, therapeutic comorbidities and treatments performed. Results: The selected case refers to a 10-year-old patient with severe ASD for 8 years. In pharmaceutical care, the main interventions were: guidance on the use of medications and prescription of supplements, such as vitamins, amino acids, fats, minerals and antioxidants. The main benefits observed were: improvement in cognition, social interaction and sensitivity to light; reduced irritability, inspiration, constipation; improved sleep and speech development. For this evaluation, instruments such as the ATEC tool and reports from the person responsible for the patient were used. Conclusion: ASD supplementation can improve symptoms such as gastrointestinal disorders, sleep disorders and cognitive functions. In this case report, the patient showed improvement in symptoms after pharmaceutical intervention with the prescription of compounded formulas.